Veterinary techniques for llamas and alpacas - Anderson, David E.; Jones, Meredyth; Miesner, Matt D. (Hoboken Wiley, 2013)
"Veterinary Techniques for Llamas and Alpacas provides a step-by-step guide to performing procedures in llamas and alpacas. Organized by body system, the book presents concise, visually oriented information to enable clinicians to treat these animals with confidence. With coverage ranging from basic maintenance such as restraint and catheterization to more complex procedures such as minimally invasive surgery, Veterinary Techniques for Llamas and Alpacas describes the full range of techniques required for the medical management of these species. Each procedure is described in detail, with a consistent format for ease of use and accompanying photographs to illustrate the concepts described. A companion website offers videos of many of the procedures discussed in the book. Veterinary Techniques for Llamas and Alpacas is an essential resource for any veterinarian or technical staff member treating South American camelid patients"--
Section I: Behavior and Capture Techniques; Section II: Physical Restraint and Injection Sites; Section III: Chemical Restraint and Anesthesia; Section IV: Catheterization; Section V: Head and Neck; Section VI: Skin; Section VII: Respiratory; Section VIII: Abdomen; Section IX: Musculoskeletal; Section X: Urinary System; Section XI: Female Genital Anatomy; Section XII: Male Genital Anatomy; Section XIII: Nervous System; Section XIV: Ophthalmology; Section XV: Miscellaneous; Index
UP System perpetual contents
Includes bibliographical references and index
Keywords: Llamas -- Diseases; Alpaca -- Diseases; Llamas -- Surgery; Alpaca -- Surgery